1993
DOI: 10.2307/1939930
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Related ^(13)C of Tree Leaves and Soil Organic Matter in a Temperate Forest

Abstract: In order to relate the isotopic composition of soil organic matter to parent vegetation and soil type, we measured the carbon stable isotope ratios of tree leaves and soil Cat 14 locations in a temperate forest. Sites were selected over a wide variety of soil types and related vegetation associations, but within a single regional climate. The o 13 C of the bulk leaf material falling on the soil varied among sites, ranging from -29.5 to -26o/oo. Within this range, differences up to 1.5o/oo were attributable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
196
2
16

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(239 citation statements)
references
References 23 publications
25
196
2
16
Order By: Relevance
“…The largest enrichment of 13 C was therefore associated with the SOC present in the H 2 O 2 resistant residue after LF removal. These results are in accord with other studies that documented enrichment of heavier 13 C compared to lighter 12 C with increasing degree of SOM decomposition (Nadelhoffer and Fry 1988;Balesdent et al 1993;Bernoux et al 1998). Such a trend in d 13 C signatures was not observed in soils from cultivated sites, where the d 13 C signatures of contemporary plant inputs are a mixture of both C 3 native species (average d 13 C of -27%) and C 4 corn (average d 13 C of -12%) ( Table 5).…”
Section: Isotopic Analyses Of Soc Before and After Oxidationsupporting
confidence: 92%
“…The largest enrichment of 13 C was therefore associated with the SOC present in the H 2 O 2 resistant residue after LF removal. These results are in accord with other studies that documented enrichment of heavier 13 C compared to lighter 12 C with increasing degree of SOM decomposition (Nadelhoffer and Fry 1988;Balesdent et al 1993;Bernoux et al 1998). Such a trend in d 13 C signatures was not observed in soils from cultivated sites, where the d 13 C signatures of contemporary plant inputs are a mixture of both C 3 native species (average d 13 C of -27%) and C 4 corn (average d 13 C of -12%) ( Table 5).…”
Section: Isotopic Analyses Of Soc Before and After Oxidationsupporting
confidence: 92%
“…For instance, Del Galdo et al (2003) found that the δ 13 C values of organic carbon in the soil profiles of forests or grass generally increased with increasing soil depth, and attributed this mainly to the isotope fractionation during litter decomposition and humification instead of the physical and chemical properties of soil. These results have also been ascribed to the tendency of microbes to utilize compounds containing 12 C rather than 13 C (Balesdent et al, 1993). The surface SOM is basically composed of newly supplemented unstable organic carbon.…”
Section: Natural Abundance Of 13 C In Doc and Dominant Plant Speciesmentioning
confidence: 98%
“…The analytical precision for these data is ±0.24‰ based upon repeated measurements of an in-house standard, which was used to correct raw measured values to the VPDB scale. The bulk sediment organic carbon δ 13 C record is interpreted as reflecting the δ 13 C value of the surrounding vegetation at the time of deposition with little to no isotopic enrichment during diagenesis (Balesdent et al, 1993), and provides a record of changes in the relative abundance of C 3 /C 4 plants to which we can compare our tooth isotope data.…”
Section: Bulk Organic Carbonmentioning
confidence: 99%